Analisis Putusan Pengadilan Negeri Bandung Nomor: 162/Pdt.G/2021/Pnbdg Tentang Legalitas Akta Perjanjian Jual Beli Sebagai Jaminan Hutang Piutang Karena Adanya Cacat Hukum - Agi Ahmad Najih; Fauzan Ali Rasyid; Muhammad Kholid (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The problem of the legality of the agreement of the deed of debt and credit agreement into buying and selling requires legal certainty so that no one is harmed. Normative legal certainty is when a regulation is made and promulgated with certainty because it regulates clearly and logically. Clear in the sense that it does not cause doubt (multi-interpretation) and logical in the sense that it becomes a system of norms with other norms so that it does not clash or cause norm conflicts. Norm conflict arising from rule uncertainty can take the form of norm contestation, norm reduction or norm distortion. This research approach is descriptive analytical which describes legal events that occur as they are and conveys these conditions according to theory and legislation. The research method used in the research is empirical juridical which analyzes the Bandung District Court Decision Number: 162/PDT.G/2021/PN.BDG regarding the Legality of the Deed of Sale and Purchase Agreement as Collateral for Debt and Credit Due to Legal Defects. The results of this study show that; AJB, which should be a proof of transfer of land rights in a real sale and purchase transaction, in this case is used to guarantee debt repayment. This is a deviation from the function of the AJB, which is legally unjustified because it contradicts the principle of halal causa (Articles 1335 and 1337 of the Civil Code). Therefore, the AJB made does not meet the elements of a valid causa, and therefore can be canceled or even null and void.